Intracellular Transport of Plant Toxins Ricin and Viscumin from Different Plasma Membrane Sites - Moisenovich, Mihail; Agapov, Igor; Marx, Uwe; Bereiter-Hahn, Jürgen; Tonevitsky, Alexander (Arzneimittelforschung, 2003)
Binding of ricin and viscumin to paraformaldehyde fixed cell surface has been studied by confocal laser scanning microscopy (CLSM). Both toxins were labeled with different fluorochromes to allow for their identification after being applied jointly. The experiments indicated that viscumin and ricin bind to different cell receptors. Viscumin bound to the very periphery of the cells including lamellapodia and cell contact regions. Labeled ricin became localized in surface clusters located close to the cell body.The binding of toxins to the cell membrane was completely inhibited by 100 mmol/l lactose and in the presence of unlabeled homological toxins 500 times in abundance of the fluorochromed toxins. The experiments indicate that uptake and intracellular transport of ricin and viscumin starts from different membrane sites.
Keywords: Mistletoe lectins; Ricin, intracellular transport; Viscumin, intracellular transport